The Relationship Between Knowledge and Attitudes of Patients Level Compliance with Protocol Implementation Covid-19 Health On Pandemic Period In R S Mata Undaan Surabaya - Agus Priyanto; Titik Juwariyah; Eko Dian Hs (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
COVID-19 is a global health problem today. Many people do not comply with health protocols consistently so that confirmed cases of covid-19 are getting higher. This is due to low knowledge and poor attitude towards efforts to prevent the spread of covid-19. The purpose of the study was to determine the relationship between knowledge and patient attitudes with the level of compliance in carrying out the covid-19 health protocol during the pandemic at the RS Mata Undaan Surabaya. The research method uses correlational descriptive with a cross sectional design. The population is patients at the RS Mata Undaan Surabaya, amounted to 280 people. Samples were taken as many as 165 people using the Probability Sampling technique with Simple Random Sampling. The independent variable is knowledge and attitude, the dependent variable is compliance. The instrument used a questionnaire, analyzed using the Spearman Rho correlation test. The results showed that most of the patients had sufficient knowledge as many as 96 people (58.2%), sufficient attitude as many as 113 people (68.5%), and a moderate level of compliance as many as 117 people (70.9%). The conclusion of this study is that there is a relationship between knowledge and attitudes of patients with the level of compliance with the Covid-19 health protocol during the pandemic at the RS Mata Undaan Surabaya with a p-value of 0.000 (ρ < α = 0.05). The implication of the research is to minimize the spread of COVID-19 by consistently implementing the COVID-19 health protocol.